High-thermal-conductivity PERT floor heating pipe and preparation method thereof
By using thermal composite filler of graphite nanosheets and aluminum nitride in floor heating pipes and anti-fouling additives of modified carbon nanotubes, the thermal conductivity and anti-bacterial and anti-fouling ability are improved, and the lack of thermal conductivity and dirt adhesion of traditional floor heating pipes is solved. The problem of achieving more efficient heating and longer service life.
Patent Information
- Application Number
- CN202411218357.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-02
AI Technical Summary
Traditional floor heating pipes have low thermal conductivity and are easily affected by oxygen and bacteria in water during long-term use, resulting in dirt adhesion and affecting heat dissipation efficiency and service life.
The thermally conductive outer layer and anti-fouling inner layer structure are used. The thermally conductive composite filler made of graphite nanosheets and surface-treated aluminum nitride is added to the thermally conductive outer layer. The anti-fouling inner layer is added with modified and modified carbon nanotubes. Dirt additives improve thermal conductivity and antibacterial and anti-scaling ability.
It has achieved the improvement of high thermal conductivity and mechanical properties, maintained good performance for long-term use and anti-bacterial and anti-scaling effects, and avoided dirt adhesion and bacterial residue.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of floor heating pipes, and in particular relates to a high thermal conductivity PERT floor heating pipe and a preparation method thereof. Background Art
[0002] The cold climate in many cities in winter often requires home heating to maintain a comfortable indoor temperature. Floor heating, also known as floor radiant heating, is commonly used for home heating. It heats the entire floor by burying hot water pipes or heating cables under the floor, and evenly transfers heat to the room through radiant heat dissipation. As a common heating method, floor heating is widely used in new buildings. Traditional floor heating pipes usually use PERT resin. This heat-resistant polyethylene resin has good toughness, low-temperature impact resistance and water pressure resistance, and is very suitable as the main material in the heating system. However, the thermal conductivity of PERT resin itself is relatively low (compared to metal pipes), and the thermal conductivity of the resin will be further affected by friction or static electricity. In addition, it is easily affected by oxygen and bacteria in the water during long-term use, which is easy to produce dirt, seriously affecting the heat dissipation efficiency and service life of the floor heating pipe, as well as the sanitation of the indoor environment.
[0003] In order to solve the above problems, the prior art adds anti-fouling or heat-conducting fillers, such as silane materials, to the PERT resin to improve the hydrophobicity of the inner wall of the pipe, prevent impurities and bacteria in the water from adhering to the inner wall of the pipe, and reduce the adhesion and deposition of dirt. The thermal conductor can increase the thermal conductivity of the pipe, accelerate heat conduction to improve the heating efficiency of the floor, and make the heating more uniform. Chinese patent CN106589547A discloses a PERT floor heating pipe and its preparation method and application. The floor heating pipe uses type II heat-resistant polyethylene or type I heat-resistant polyethylene as the main material, and improves the thermal conductivity and thermal conductivity of the floor heating pipe by adding fillers such as graphite and carbon fiber, reduces the expansion coefficient and shrinkage rate of the pipe, and can be widely used for floor heating. However, these fillers often have poor compatibility with the main material PERT resin, which has an adverse effect on the overall performance and stability of the floor heating pipe. Therefore, the present invention aims to prepare a new type of high thermal conductivity PERT floor heating pipe to solve the problems of anti-fouling and insufficient thermal conductivity in the prior art, thereby providing a more efficient heating experience, and being able to maintain good performance and reliability during long-term use, further meeting people's needs for a comfortable indoor environment. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a high thermal conductivity PERT floor heating pipe, including a thermal conductive outer layer and an anti-fouling inner layer, by adding a thermal conductive composite filler made of graphite nanosheets and surface-treated aluminum nitride to the raw material of the thermal conductive outer layer, and adding an anti-fouling additive made of modified and halogenated carbon nanotubes to the raw material of the anti-fouling inner layer, while ensuring that the PERT floor heating pipe has excellent thermal conductivity and mechanical properties, it can also be antibacterial and anti-fouling, and can maintain good performance during long-term use. The present invention also provides a preparation method of the above-mentioned high thermal conductivity PERT floor heating pipe.
[0005] A high thermal conductivity PERT floor heating pipe, comprising a thermal conductive outer layer and an anti-fouling inner layer;
[0006] Preferably, the thermally conductive outer layer is made of the following raw materials in parts by weight: 200-500 parts of PERT resin, 5-15 parts of thermally conductive composite filler, 1-5 parts of plasticizer, 0.5-3.5 parts of antioxidant, and 2-5 parts of compatibilizer.
[0007] Preferably, the anti-fouling inner layer is made of the following raw materials in parts by weight: 100-200 parts of PERT resin, 3-8 parts of anti-fouling additive, 1-2 parts of plasticizer, 0.5-1.5 parts of antioxidant, and 1-2 parts of compatibilizer.
[0008] Preferably, the thickness of the heat-conducting outer layer is 1-3 mm, and the thickness of the anti-fouling inner layer is 0.5-2 mm.
[0009] Preferably, the plasticizer is one or a mixture of two or more of polyethylene wax, chlorinated paraffin, dioctyl phthalate, acetyl tributyl citrate, and di(2-ethylhexyl) adipate.
[0010] Preferably, the antioxidant is one of antioxidant DSTP, antioxidant 1076, antioxidant 1010, antioxidant 1098, and antioxidant 636, or a mixture of two or more thereof.
[0011] Preferably, the compatibilizer is one or a mixture of two or more of polyethylene grafted maleic anhydride, polypropylene grafted maleic anhydride, and polyolefin elastomer grafted maleic anhydride.
[0012] Preferably, the preparation method of the thermally conductive composite filler is as follows:
[0013] 0.1-0.5 parts by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 0.1-0.5 parts by weight of 3-diethylenetriaminopropylmethyldimethoxysilane, 1-3 parts by weight of ammonium octadecanoate and 3-6 parts by weight of acetic acid are added to methanol and water and mixed evenly, then 10-30 parts by weight of aluminum nitride are added, heated and stirred, centrifuged, washed and dried to obtain surface-treated aluminum nitride; 15-20 parts by weight of graphite nanosheets and 5-10 parts by weight of surface-treated aluminum nitride are added to N,N-dimethylformamide and mixed evenly, heated and stirred, centrifuged, washed and dried, and then calcined under nitrogen protection to obtain a thermally conductive composite filler.
[0014] The thermally conductive composite filler prepared by the present invention is based on the precise control and regulation of graphite nanosheets and surface-treated aluminum nitride. In the preparation process of the composite filler, a surface treatment liquid composed of 3-(2,3-epoxypropyloxy)propyltrimethoxysilane and 3-diethylenetriaminopropylmethyldimethoxysilane is used to perform surface modification treatment on aluminum nitride, so that its surface carries a positive charge, and this positive charge attracts the negative charge on the surface of the graphite nanosheet, and promotes the self-assembly between the two through electrostatic action and chemical bonding. Therefore, the graphite nanosheet is uniformly coated in the covering layer formed on the surface of the aluminum nitride. This self-assembly process not only improves the compatibility and dispersibility of the graphite nanosheet with the matrix, but also improves the stability of the filler. In addition, the graphite nanosheet itself has high thermal conductivity, so after it is composited with the surface-treated aluminum nitride, the thermal conductivity of the filler as a whole is significantly improved. As a part of the matrix, aluminum nitride not only maintains high strength and high thermal conductivity, but is also further improved through surface treatment to ensure its effective combination with the graphite nanosheet. In summary, the composite filler not only has the advantage of high thermal conductivity of graphite nanosheets, but also overcomes its problems such as dispersibility and poor compatibility with the matrix. The components in the filler achieve synergistic effects, making the filler structure more stable, thereby achieving an improvement in the overall thermal conductivity.
[0015] Preferably, the preparation method of the thermally conductive composite filler is as follows:
[0016] 0.1-0.5 parts by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 0.1-0.5 parts by weight of 3-divinyltriaminopropylmethyldimethoxysilane, 1-3 parts by weight of ammonium octadecanoate and 3-6 parts by weight of acetic acid are added to 50-80 parts by weight of methanol and 30-50 parts by weight of water and mixed evenly, then 10-30 parts by weight of aluminum nitride are added, stirred at 75-85° C. for 5-10 hours, centrifuged, washed and dried to obtain surface-treated aluminum nitride; 15-20 parts by weight of graphite nanosheets and 5-10 parts by weight of surface-treated aluminum nitride are added to 100-300 parts by weight of N,N-dimethylformamide and mixed evenly, stirred at 40-50° C. for 2-5 hours, centrifuged, washed and dried, and then calcined at 1100-1300° C. under nitrogen protection for 1-3 hours to obtain a thermally conductive composite filler.
[0017] Preferably, the aluminum nitride is composed of aluminum nitride with a particle size of 2-10 μm and aluminum nitride with a particle size of 40-50 μm in a weight ratio of 1:1-2.
[0018] Preferably, the preparation method of the anti-fouling aid is as follows:
[0019] 1-5 parts by weight of carbon nanotubes are added to N,N-dimethylformamide and mixed evenly, then 10-15 parts by weight of vinyl triethoxysilane are added, heated and stirred, centrifuged, washed and dried to obtain vinyl carbon nanotubes; 0.2-0.5 parts by weight of sodium dodecylbenzene sulfonate and 1-2 parts by weight of vinyl carbon nanotubes are added to water and mixed evenly, then 0.5-1.5 parts by weight of 4-vinylpiperidine hydrochloride, 1-1.5 parts by weight of butyl methacrylate and 0.1-0.3 parts by weight of azobisisobutyronitrile are added, heated and reacted under nitrogen protection, centrifuged, washed and dried to obtain piperidine-modified carbon nanotubes; 0.5-2 parts by weight of piperidine-modified carbon nanotubes and 0.5-2 parts by weight of sodium hypochlorite are added to water and mixed evenly, stirred at room temperature, centrifuged, washed and dried to obtain an antifouling agent. Preferably, the carbon nanotubes are hydroxylated multi-walled carbon nanotubes.
[0020] The present invention firstly introduces ethylene into the surface of carbon nanotubes by grafting reaction of vinyl triethoxysilane with hydroxyl groups on the surface of carbon nanotubes, thereby introducing vinyl groups. This step chemically modifies the surface of carbon nanotubes, providing a basis for subsequent modification. Then, under the action of initiator azobisisobutyronitrile, monomers 4-vinylpiperidine hydrochloride and butyl methacrylate undergo in-situ graft polymerization on the surface of carbon nanotubes to obtain piperidine-modified carbon nanotubes, further improving the surface properties and compatibility of carbon nanotubes. Finally, halogenated with sodium hypochlorite, halamine antibacterial carbon nanotubes are obtained, which are used as antifouling additives for the inner layer of PERT floor heating pipes. On the one hand, the grafted halamine antibacterial structure has excellent antibacterial ability, which can make the inner side of the floor heating pipe wall free of bacteria residues, significantly improving the antibacterial and anti-scaling properties of the pipes. On the other hand, through this series of treatment steps, the agglomeration and dispersibility of carbon nanotubes are improved, and the interface compatibility with the matrix is enhanced, avoiding the adverse effects of direct addition on the mechanical and other comprehensive properties of the pipes. In addition, the present invention also utilizes the interaction between two aluminum nitrides of different particle sizes to better increase the thermal conductivity of the thermally conductive filler. This may be because the use of two aluminum nitrides of different particle sizes helps to form a tighter network structure in the system, thereby improving the overall thermal conductivity of the pipe.
[0021] Preferably, the preparation method of the anti-fouling aid is as follows:
[0022] 1-5 parts by weight of carbon nanotubes are added to 100-200 parts by weight of N,N-dimethylformamide and mixed evenly, then 10-15 parts by weight of vinyl triethoxysilane are added, stirred at 125-135° C. for 50-70 hours, centrifuged, washed, and dried to obtain vinyl carbon nanotubes; 0.2-0.5 parts by weight of sodium dodecylbenzene sulfonate and 1-2 parts by weight of vinyl carbon nanotubes are added to 80-120 parts by weight of water and mixed evenly, then 0.5-1.5 Parts by weight of 4-vinylpiperidine hydrochloride, 1-1.5 parts by weight of butyl methacrylate and 0.1-0.3 parts by weight of azobisisobutyronitrile are reacted at 85-95° C. under nitrogen protection for 2-5 hours, centrifuged, washed and dried to obtain piperidine-modified carbon nanotubes; 0.5-2 parts by weight of piperidine-modified carbon nanotubes and 0.5-2 parts by weight of sodium hypochlorite are added to 50-100 parts by weight of water, mixed evenly, stirred at room temperature for 5-10 hours, centrifuged, washed and dried to obtain an antifouling additive.
[0023] The present invention also provides a method for preparing the above-mentioned high thermal conductivity PERT floor heating pipe, comprising the following steps:
[0024] According to the raw material formula, the raw materials in the heat-conducting outer layer and the anti-fouling inner layer are mixed to obtain the heat-conducting outer layer mixed material and the anti-fouling inner layer mixed material; then the heat-conducting outer layer mixed material and the anti-fouling inner layer mixed material are subjected to two-layer extrusion, sizing, molding, pulling and cutting to obtain the high thermal conductivity PERT floor heating pipe. The extrusion temperature is 190-210°C.
[0025] Beneficial effects of the present invention:
[0026] The present invention provides a preparation method of a PERT floor heating pipe. By adding a thermally conductive composite filler made of graphite nanosheets and surface-treated aluminum nitride into a thermally conductive outer layer raw material, and adding an anti-fouling additive made of modified and halogenated carbon nanotubes into an anti-fouling inner layer raw material, the PERT floor heating pipe not only has excellent thermal conductivity and mechanical properties, but also is antibacterial and anti-scaling, and can maintain good performance during long-term use. DETAILED DESCRIPTION
[0027] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] A high thermal conductivity PERT floor heating pipe, comprising a thermal conductive outer layer and an anti-fouling inner layer;
[0030] The thermally conductive outer layer is made of the following raw materials in parts by weight: 300 parts by weight of PERT resin (density 0.937 g / cm 3 , melt index 0.6g / 10min), 8.5 parts by weight of thermal conductive composite filler, 2.6 parts by weight of plasticizer acetyl tributyl citrate, 2 parts by weight of antioxidant 1010, and 3 parts by weight of compatibilizer polyethylene grafted maleic anhydride (CAS:9006-26-2).
[0031] The preparation method of the thermally conductive composite filler is as follows:
[0032] 0.2 parts by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane (CAS: 2530-83-8), 0.3 parts by weight of 3-diethylenetriaminopropylmethyldimethoxysilane (CAS: 99740-64-4), 2 parts by weight of ammonium octadecanoate (CAS: 1002-89-7), and 5 parts by weight of acetic acid were added to 60 parts by weight of methanol and 40 parts by weight of water and mixed evenly, and then 20 parts by weight of aluminum nitride (made of aluminum nitride with a particle size of 5 μm and aluminum nitride with a particle size of 10 μm) were added to the mixture. 45μm aluminum nitride in a weight ratio of 1:1.5), stirred at 82°C for 7h, centrifuged, washed, and dried to obtain surface-treated aluminum nitride; 18 parts by weight of graphite nanosheets (GNP thickness ≤ 15nm) and 7.5 parts by weight of surface-treated aluminum nitride were added to 200 parts by weight of N,N-dimethylformamide and mixed evenly, stirred at 45°C for 3h, centrifuged, washed, and dried, and then calcined at 1250°C under nitrogen protection for 2h to obtain a thermally conductive composite filler.
[0033] The anti-fouling inner layer is made of the following raw materials in parts by weight: 150 parts by weight of PERT resin (density 0.937 g / cm 3 , melt index 0.6g / 10min), 6 parts by weight of anti-fouling agent, 1.3 parts by weight of plasticizer acetyl tributyl citrate, 1 part by weight of antioxidant 1010, and 1.5 parts by weight of compatibilizer polyethylene grafted maleic anhydride (CAS:9006-26-2).
[0034] The preparation method of the anti-fouling aid is as follows:
[0035] 2.5 parts by weight of carbon nanotubes are added to 150 parts by weight of N,N-dimethylformamide and mixed evenly, then 12 parts by weight of vinyl triethoxysilane are added, stirred at 130°C for 60 hours, centrifuged, washed, and dried to obtain vinyl carbon nanotubes; wherein the carbon nanotubes are hydroxylated multi-walled carbon nanotubes with a length of 0.5-2 μm, an inner diameter of 2-5 nm, an outer diameter of 5-15 nm, and a hydroxyl content of 5.6 wt%; 0.4 parts by weight of sodium dodecylbenzene sulfonate and 1.5 parts by weight of vinyl carbon nanotubes are added to 10 0.5 parts by weight of carbon nanotubes modified with piperidine were added to 1 part by weight of water, and then 1 part by weight of 4-vinylpiperidinium hydrochloride (CAS: 1311316-95-6), 1.2 parts by weight of butyl methacrylate and 0.25 parts by weight of azobisisobutyronitrile were added, and the mixture was reacted at 90° C. under nitrogen protection for 3 h, and the mixture was centrifuged, washed and dried to obtain piperidine-modified carbon nanotubes; 0.85 parts by weight of piperidine-modified carbon nanotubes and 1 part by weight of sodium hypochlorite were added to 60 parts by weight of water, and the mixture was mixed evenly, and the mixture was stirred at room temperature for 6 h, and the mixture was centrifuged, washed and dried to obtain an antifouling additive.
[0036] A method for preparing a high thermal conductivity PERT floor heating pipe comprises the following steps:
[0037] According to the raw material formula, the raw materials in the heat-conducting outer layer and the anti-fouling inner layer are mixed to obtain the heat-conducting outer layer mixed material and the anti-fouling inner layer mixed material; then the heat-conducting outer layer mixed material and the anti-fouling inner layer mixed material are subjected to two-layer extrusion, sizing, molding, pulling and cutting to obtain the high thermal conductivity PERT floor heating pipe. The extrusion temperature is 190-210°C, the thickness of the heat-conducting outer layer is 2mm, and the thickness of the anti-fouling inner layer is 1mm.
[0038] Example 2
[0039] A high thermal conductivity PERT floor heating pipe, comprising a thermal conductive outer layer and an anti-fouling inner layer;
[0040] The thermally conductive outer layer is made of the following raw materials in parts by weight: 300 parts by weight of PERT resin (density 0.937 g / cm 3 , melt index 0.6g / 10min), 8.5 parts by weight of thermal conductive composite filler, 2.6 parts by weight of plasticizer acetyl tributyl citrate, 2 parts by weight of antioxidant 1010, and 3 parts by weight of compatibilizer polyethylene grafted maleic anhydride (CAS:9006-26-2).
[0041] The preparation method of the thermally conductive composite filler is as follows:
[0042] 18 parts by weight of graphite nanosheets (GNP thickness ≤ 15 nm) and 7.5 parts by weight of aluminum nitride (composed of aluminum nitride with a particle size of 5 μm and aluminum nitride with a particle size of 45 μm in a weight ratio of 1:1.5) are added to 200 parts by weight of N,N-dimethylformamide and mixed evenly, stirred at 45°C for 3 hours, centrifuged, washed, and dried, and then calcined at 1250°C under nitrogen protection for 2 hours to obtain a thermally conductive composite filler.
[0043] The anti-fouling inner layer is made of the following raw materials in parts by weight: 150 parts by weight of PERT resin (density 0.937 g / cm 3 , melt index 0.6g / 10min), 6 parts by weight of anti-fouling agent, 1.3 parts by weight of plasticizer acetyl tributyl citrate, 1 part by weight of antioxidant 1010, and 1.5 parts by weight of compatibilizer polyethylene grafted maleic anhydride (CAS:9006-26-2).
[0044] The preparation method of the anti-fouling aid is as follows:
[0045] 2.5 parts by weight of carbon nanotubes are added to 150 parts by weight of N,N-dimethylformamide and mixed evenly, then 12 parts by weight of vinyl triethoxysilane are added, stirred at 130°C for 60 hours, centrifuged, washed, and dried to obtain vinyl carbon nanotubes; wherein the carbon nanotubes are hydroxylated multi-walled carbon nanotubes with a length of 0.5-2 μm, an inner diameter of 2-5 nm, an outer diameter of 5-15 nm, and a hydroxyl content of 5.6 wt%; 0.4 parts by weight of sodium dodecylbenzene sulfonate and 1.5 parts by weight of vinyl carbon nanotubes are added to 10 0.5 parts by weight of carbon nanotubes modified with piperidine were added to 1 part by weight of water, and then 1 part by weight of 4-vinylpiperidinium hydrochloride (CAS: 1311316-95-6), 1.2 parts by weight of butyl methacrylate and 0.25 parts by weight of azobisisobutyronitrile were added, and the mixture was reacted at 90° C. under nitrogen protection for 3 h, and the mixture was centrifuged, washed and dried to obtain piperidine-modified carbon nanotubes; 0.85 parts by weight of piperidine-modified carbon nanotubes and 1 part by weight of sodium hypochlorite were added to 60 parts by weight of water, and the mixture was mixed evenly, and the mixture was stirred at room temperature for 6 h, and the mixture was centrifuged, washed and dried to obtain an antifouling additive.
[0046] A method for preparing a high thermal conductivity PERT floor heating pipe comprises the following steps:
[0047] According to the raw material formula, the raw materials in the heat-conducting outer layer and the anti-fouling inner layer are mixed to obtain the heat-conducting outer layer mixed material and the anti-fouling inner layer mixed material; then the heat-conducting outer layer mixed material and the anti-fouling inner layer mixed material are subjected to two-layer extrusion, sizing, molding, pulling and cutting to obtain the high thermal conductivity PERT floor heating pipe. The extrusion temperature is 190-210°C, the thickness of the heat-conducting outer layer is 2mm, and the thickness of the anti-fouling inner layer is 1mm.
[0048] Example 3
[0049] A high thermal conductivity PERT floor heating pipe, comprising a thermal conductive outer layer and an anti-fouling inner layer;
[0050] The thermally conductive outer layer is made of the following raw materials in parts by weight: 300 parts by weight of PERT resin (density 0.937 g / cm 3 , melt index 0.6g / 10min), 8.5 parts by weight of thermal conductive composite filler, 2.6 parts by weight of plasticizer acetyl tributyl citrate, 2 parts by weight of antioxidant 1010, and 3 parts by weight of compatibilizer polyethylene grafted maleic anhydride (CAS:9006-26-2).
[0051] The preparation method of the thermally conductive composite filler is as follows:
[0052] 0.2 parts by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane (CAS: 2530-83-8), 0.3 parts by weight of 3-diethylenetriaminopropylmethyldimethoxysilane (CAS: 99740-64-4), 2 parts by weight of ammonium octadecanoate (CAS: 1002-89-7), and 5 parts by weight of acetic acid are added to 60 parts by weight of methanol and 40 parts by weight of water and mixed evenly, and then 20 parts by weight of aluminum nitride (aluminum nitride with a particle size of 5 μm) are added, stirred at 82° C. for 7 hours, centrifuged, washed, and dried to obtain surface-treated aluminum nitride; 18 parts by weight of graphite nanosheets (GNP thickness ≤ 15 nm) and 7.5 parts by weight of surface-treated aluminum nitride are added to 200 parts by weight of N, N-dimethylformamide and mixed evenly, stirred at 45° C. for 3 hours, centrifuged, washed, and dried, and then calcined at 1250° C. under nitrogen protection for 2 hours to obtain a thermally conductive composite filler.
[0053] The anti-fouling inner layer is made of the following raw materials in parts by weight: 150 parts by weight of PERT resin (density 0.937 g / cm 3 , melt index 0.6g / 10min), 6 parts by weight of anti-fouling agent, 1.3 parts by weight of plasticizer acetyl tributyl citrate, 1 part by weight of antioxidant 1010, and 1.5 parts by weight of compatibilizer polyethylene grafted maleic anhydride (CAS:9006-26-2).
[0054] The preparation method of the anti-fouling aid is as follows:
[0055] 2.5 parts by weight of carbon nanotubes are added to 150 parts by weight of N,N-dimethylformamide and mixed evenly, then 12 parts by weight of vinyl triethoxysilane are added, stirred at 130°C for 60 hours, centrifuged, washed, and dried to obtain vinyl carbon nanotubes; wherein the carbon nanotubes are hydroxylated multi-walled carbon nanotubes with a length of 0.5-2 μm, an inner diameter of 2-5 nm, an outer diameter of 5-15 nm, and a hydroxyl content of 5.6 wt%; 0.4 parts by weight of sodium dodecylbenzene sulfonate and 1.5 parts by weight of vinyl carbon nanotubes are added to 10 0.5 parts by weight of carbon nanotubes modified with piperidine were added to 1 part by weight of water, and then 1 part by weight of 4-vinylpiperidinium hydrochloride (CAS: 1311316-95-6), 1.2 parts by weight of butyl methacrylate and 0.25 parts by weight of azobisisobutyronitrile were added, and the mixture was reacted at 90° C. under nitrogen protection for 3 h, and the mixture was centrifuged, washed and dried to obtain piperidine-modified carbon nanotubes; 0.85 parts by weight of piperidine-modified carbon nanotubes and 1 part by weight of sodium hypochlorite were added to 60 parts by weight of water, and the mixture was mixed evenly, and the mixture was stirred at room temperature for 6 h, and the mixture was centrifuged, washed and dried to obtain an antifouling additive.
[0056] A method for preparing a high thermal conductivity PERT floor heating pipe comprises the following steps:
[0057] According to the raw material formula, the raw materials in the heat-conducting outer layer and the anti-fouling inner layer are mixed to obtain the heat-conducting outer layer mixed material and the anti-fouling inner layer mixed material; then the heat-conducting outer layer mixed material and the anti-fouling inner layer mixed material are subjected to two-layer extrusion, sizing, molding, pulling and cutting to obtain the high thermal conductivity PERT floor heating pipe. The extrusion temperature is 190-210°C, the thickness of the heat-conducting outer layer is 2mm, and the thickness of the anti-fouling inner layer is 1mm.
[0058] Example 4
[0059] A high thermal conductivity PERT floor heating pipe, comprising a thermal conductive outer layer and an anti-fouling inner layer;
[0060] The thermally conductive outer layer is made of the following raw materials in parts by weight: 300 parts by weight of PERT resin (density 0.937 g / cm 3 , melt index 0.6g / 10min), 8.5 parts by weight of thermal conductive composite filler, 2.6 parts by weight of plasticizer acetyl tributyl citrate, 2 parts by weight of antioxidant 1010, and 3 parts by weight of compatibilizer polyethylene grafted maleic anhydride (CAS:9006-26-2).
[0061] The preparation method of the thermally conductive composite filler is as follows:
[0062] 0.2 parts by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane (CAS: 2530-83-8), 0.3 parts by weight of 3-diethylenetriaminopropylmethyldimethoxysilane (CAS: 99740-64-4), 2 parts by weight of ammonium octadecanoate (CAS: 1002-89-7), and 5 parts by weight of acetic acid were added to 60 parts by weight of methanol and 40 parts by weight of water and mixed evenly, and then 20 parts by weight of aluminum nitride (made of aluminum nitride with a particle size of 5 μm and aluminum nitride with a particle size of 10 μm) were added to the mixture. 45μm aluminum nitride in a weight ratio of 1:1.5), stirred at 82°C for 7h, centrifuged, washed, and dried to obtain surface-treated aluminum nitride; 18 parts by weight of graphite nanosheets (GNP thickness ≤ 15nm) and 7.5 parts by weight of surface-treated aluminum nitride were added to 200 parts by weight of N,N-dimethylformamide and mixed evenly, stirred at 45°C for 3h, centrifuged, washed, and dried, and then calcined at 1250°C under nitrogen protection for 2h to obtain a thermally conductive composite filler.
[0063] The anti-fouling inner layer is made of the following raw materials in parts by weight: 150 parts by weight of PERT resin (density 0.937 g / cm 3 , melt index 0.6g / 10min), 6 parts by weight of anti-fouling agent, 1.3 parts by weight of plasticizer acetyl tributyl citrate, 1 part by weight of antioxidant 1010, and 1.5 parts by weight of compatibilizer polyethylene grafted maleic anhydride (CAS:9006-26-2).
[0064] The preparation method of the anti-fouling aid is as follows:
[0065] 0.85 parts by weight of carbon nanotubes and 1 part by weight of sodium hypochlorite were added to 60 parts by weight of water and mixed evenly, stirred at room temperature for 6 hours, centrifuged, washed, and dried to obtain an antifouling agent, wherein the carbon nanotubes were hydroxylated multi-walled carbon nanotubes with a length of 0.5-2 μm, an inner diameter of 2-5 nm, an outer diameter of 5-15 nm, and a hydroxyl content of 5.6 wt%.
[0066] A method for preparing a high thermal conductivity PERT floor heating pipe comprises the following steps:
[0067] According to the raw material formula, the raw materials in the heat-conducting outer layer and the anti-fouling inner layer are mixed to obtain the heat-conducting outer layer mixed material and the anti-fouling inner layer mixed material; then the heat-conducting outer layer mixed material and the anti-fouling inner layer mixed material are subjected to two-layer extrusion, sizing, molding, pulling and cutting to obtain the high thermal conductivity PERT floor heating pipe. The extrusion temperature is 190-210°C, the thickness of the heat-conducting outer layer is 2mm, and the thickness of the anti-fouling inner layer is 1mm.
[0068] Example 5
[0069] A high thermal conductivity PERT floor heating pipe, comprising a thermal conductive outer layer and an anti-fouling inner layer;
[0070] The thermally conductive outer layer is made of the following raw materials in parts by weight: 300 parts by weight of PERT resin (density 0.937 g / cm 3 , melt index 0.6g / 10min), 8.5 parts by weight of thermal conductive composite filler, 2.6 parts by weight of plasticizer acetyl tributyl citrate, 2 parts by weight of antioxidant 1010, and 3 parts by weight of compatibilizer polyethylene grafted maleic anhydride (CAS:9006-26-2).
[0071] The preparation method of the thermally conductive composite filler is as follows:
[0072] 0.2 parts by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane (CAS: 2530-83-8), 0.3 parts by weight of 3-diethylenetriaminopropylmethyldimethoxysilane (CAS: 99740-64-4), 2 parts by weight of ammonium octadecanoate (CAS: 1002-89-7), and 5 parts by weight of acetic acid were added to 60 parts by weight of methanol and 40 parts by weight of water and mixed evenly, and then 20 parts by weight of aluminum nitride (made of aluminum nitride with a particle size of 5 μm and aluminum nitride with a particle size of 10 μm) were added to the mixture. 45μm aluminum nitride in a weight ratio of 1:1.5), stirred at 82°C for 7h, centrifuged, washed, and dried to obtain surface-treated aluminum nitride; 18 parts by weight of graphite nanosheets (GNP thickness ≤ 15nm) and 7.5 parts by weight of surface-treated aluminum nitride were added to 200 parts by weight of N,N-dimethylformamide and mixed evenly, stirred at 45°C for 3h, centrifuged, washed, and dried, and then calcined at 1250°C under nitrogen protection for 2h to obtain a thermally conductive composite filler.
[0073] The anti-fouling inner layer is made of the following raw materials in parts by weight: 150 parts by weight of PERT resin (density 0.937 g / cm 3 , melt index 0.6g / 10min), 6 parts by weight of anti-fouling agent, 1.3 parts by weight of plasticizer acetyl tributyl citrate, 1 part by weight of antioxidant 1010, and 1.5 parts by weight of compatibilizer polyethylene grafted maleic anhydride (CAS:9006-26-2).
[0074] The preparation method of the anti-fouling aid is as follows:
[0075] 2.5 parts by weight of carbon nanotubes are added to 150 parts by weight of N,N-dimethylformamide and mixed evenly, then 12 parts by weight of vinyltriethoxysilane are added, stirred at 130°C for 60 hours, centrifuged, washed, and dried to obtain vinyl carbon nanotubes; wherein the carbon nanotubes are hydroxylated multi-walled carbon nanotubes with a length of 0.5-2 μm, an inner diameter of 2-5 nm, an outer diameter of 5-15 nm, and a hydroxyl content of 5.6 wt%; 0.85 parts by weight of vinyl carbon nanotubes and 1 part by weight of sodium hypochlorite are added to 60 parts by weight of water and mixed evenly, stirred at room temperature for 6 hours, centrifuged, washed, and dried to obtain an anti-fouling agent.
[0076] A method for preparing a high thermal conductivity PERT floor heating pipe comprises the following steps:
[0077] According to the raw material formula, the raw materials in the heat-conducting outer layer and the anti-fouling inner layer are mixed to obtain the heat-conducting outer layer mixed material and the anti-fouling inner layer mixed material; then the heat-conducting outer layer mixed material and the anti-fouling inner layer mixed material are subjected to two-layer extrusion, sizing, molding, pulling and cutting to obtain the high thermal conductivity PERT floor heating pipe. The extrusion temperature is 190-210°C, the thickness of the heat-conducting outer layer is 2mm, and the thickness of the anti-fouling inner layer is 1mm.
[0078] Test Example 1
[0079] The thermal conductivity of the above examples was measured according to GB / T3399-1982 "Test method for thermal conductivity of plastics - Guarded hot plate method"; the tensile strength of the above examples was measured according to GB / T1040.2-2022 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics".
[0080] Table 1. Tensile strength and thermal conductivity of floor heating pipes
[0081] Tensile strength(Mpa) Thermal conductivity (W / m·k) Example 1 30.8 1.60 Example 2 26.5 1.12 Example 3 29.0 1.38
[0082] Test Example 2
[0083] The anti-fouling performance and hydrostatic pressure resistance of the above examples were measured with reference to GB / T28799.2-2020 "Heat-resistant polyethylene (PE-RT) piping system for hot and cold water Part 2: Pipes".
[0084] Table 2. Anti-fouling and hydrostatic performance of floor heating pipes
[0085]
[0086] It can be seen that the PERT floor heating pipe prepared by the present invention not only has excellent mechanical properties and high thermal conductivity, but also has good antibacterial and anti-scaling capabilities, and keeps the inner wall free of dirt during long-term use, and does not have leakage and rupture problems. Compared with Examples 2-3, the thermally conductive composite filler used in Example 1 is based on the precise control and regulation of graphite nanosheets and surface-treated aluminum nitride. The surface treatment liquid composed of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 3-diethylenetriaminopropylmethyldimethoxysilane is used to modify the surface of aluminum nitride so that its surface carries a positive charge. This positive charge attracts the negative charge on the surface of the graphite nanosheet, and promotes self-assembly between the two through electrostatic action and chemical bonding. The graphite nanosheets are evenly coated in the covering layer formed on the surface of the aluminum nitride, which not only improves the compatibility and dispersibility of the graphite nanosheets and the matrix, but also improves the stability of the filler. This composite filler not only has the advantage of high thermal conductivity of graphite nanosheets, but also overcomes its problems such as dispersibility and poor compatibility with the matrix. The components in the filler achieve synergistic effects, making the filler structure more stable, thereby achieving an improvement in the overall thermal conductivity. Compared with Examples 4-5, the anti-fouling agent used in Example 1 first introduces vinyl groups into the surface of carbon nanotubes by grafting reaction of vinyltriethoxysilane with hydroxyl groups on the surface of carbon nanotubes. Then, under the action of initiator azobisisobutyronitrile, monomers 4-vinylpiperidine hydrochloride and butyl methacrylate undergo in situ grafting polymerization on the surface of carbon nanotubes to obtain piperidine-modified carbon nanotubes, further improving the surface properties and compatibility of carbon nanotubes. Finally, halogenated carbon nanotubes are obtained by sodium hypochlorite halogenation treatment to obtain halamine antibacterial carbon nanotubes, which are used as anti-fouling agents in the inner layer of PERT floor heating pipes. On the one hand, the grafted halamine antibacterial structure has excellent antibacterial ability, which can make the inner side of the floor heating pipe wall free of bacteria residues, significantly improving the antibacterial and anti-scaling properties of the pipes. On the other hand, through this series of treatment steps, the agglomeration and dispersibility of carbon nanotubes are improved, and the interface compatibility with the matrix is enhanced, avoiding the adverse effects of direct addition on the mechanical and other comprehensive properties of the pipes. In addition, the present invention also utilizes the interaction between two aluminum nitrides of different particle sizes to better increase the thermal conductivity of the thermally conductive filler. This may be because the use of two aluminum nitrides of different particle sizes helps to form a tighter network structure in the system, thereby improving the overall thermal conductivity.
[0087] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A high thermal conductivity PERT floor heating pipe, characterized in that: It comprises a heat-conductive outer layer and an anti-fouling inner layer; the heat-conductive outer layer is made of the following raw materials in parts by weight: 200-500 parts of PERT resin, 5-15 parts of heat-conductive composite filler, 1-5 parts of plasticizer, 0.5-3.5 parts of antioxidant, and 2-5 parts of compatibilizer; the heat-conductive composite filler is made of graphite nanosheets and surface-treated aluminum nitride.
2. The high thermal conductivity PERT floor heating pipe according to claim 1, characterized in that: The preparation method of the thermally conductive composite filler is as follows: 0.1-0.5 parts by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 0.1-0.5 parts by weight of 3-diethylenetriaminopropylmethyldimethoxysilane, 1-3 parts by weight of ammonium octadecanoate and 3-6 parts by weight of acetic acid are added to methanol and water and mixed evenly, then 10-30 parts by weight of aluminum nitride are added, heated and stirred, centrifuged, washed and dried to obtain surface-treated aluminum nitride; 15-20 parts by weight of graphite nanosheets and 5-10 parts by weight of surface-treated aluminum nitride are added to N,N-dimethylformamide and mixed evenly, heated and stirred, centrifuged, washed and dried, and then calcined under nitrogen protection to obtain a thermally conductive composite filler.
3. The high thermal conductivity PERT floor heating pipe according to claim 1, characterized in that: The anti-fouling inner layer is made of the following raw materials in parts by weight: 100-200 parts of PERT resin, 3-8 parts of anti-fouling additive, 1-2 parts of plasticizer, 0.5-1.5 parts of antioxidant, and 1-2 parts of compatibilizer.
4. The high thermal conductivity PERT floor heating pipe according to claim 3, characterized in that: The preparation method of the anti-fouling aid is as follows: 1-5 parts by weight of carbon nanotubes are added to N,N-dimethylformamide and mixed evenly, then 10-15 parts by weight of vinyl triethoxysilane are added, heated and stirred, centrifuged, washed and dried to obtain vinyl carbon nanotubes; 0.2-0.5 parts by weight of sodium dodecylbenzene sulfonate and 1-2 parts by weight of vinyl carbon nanotubes are added to water and mixed evenly, then 0.5-1.5 parts by weight of 4-vinylpiperidine hydrochloride, 1-1.5 parts by weight of butyl methacrylate and 0.1-0.3 parts by weight of azobisisobutyronitrile are added, heated to react under nitrogen protection, centrifuged, washed and dried to obtain piperidine-modified carbon nanotubes; 0.5-2 parts by weight of piperidine-modified carbon nanotubes and 0.5-2 parts by weight of sodium hypochlorite are added to water and mixed evenly, stirred at room temperature, centrifuged, washed and dried to obtain an anti-fouling additive.
5. The high thermal conductivity PERT floor heating pipe according to claim 2, characterized in that: The aluminum nitride is composed of aluminum nitride with a particle size of 2-10 μm and aluminum nitride with a particle size of 40-50 μm.
6. The high thermal conductivity PERT floor heating pipe according to claim 4, characterized in that: The carbon nanotubes are hydroxylated multi-walled carbon nanotubes.
7. The high thermal conductivity PERT floor heating pipe according to claim 1 or 3, characterized in that: The plasticizer is one or a mixture of two or more of polyethylene wax, chlorinated paraffin, dioctyl phthalate, acetyl tributyl citrate, and di(2-ethylhexyl) adipate.
8. The high thermal conductivity PERT floor heating pipe according to claim 1 or 3, characterized in that: The antioxidant is one of antioxidant DSTP, antioxidant 1076, antioxidant 1010, antioxidant 1098, and antioxidant 636, or a mixture of two or more thereof.
9. The high thermal conductivity PERT floor heating pipe according to claim 1 or 3, characterized in that: The compatibilizer is one or a mixture of two or more of polyethylene grafted maleic anhydride, polypropylene grafted maleic anhydride, and polyolefin elastomer grafted maleic anhydride.
10. The method for preparing the high thermal conductivity PERT floor heating pipe according to any one of claims 1 to 9, characterized in that: The following steps are involved: According to the raw material formula, the raw materials in the heat-conductive outer layer and the anti-fouling inner layer are mixed respectively to obtain the heat-conductive outer layer mixed material and the anti-fouling inner layer mixed material; then the heat-conductive outer layer mixed material and the anti-fouling inner layer mixed material are subjected to two-layer extrusion, sizing, molding, pulling and cutting to obtain the high thermal conductivity PERT floor heating pipe.
Citation Information
Patent Citations
PE-RT (polyethylene of raised temperature resistance) floor heating pipe and production method and application thereof
CN106589547A
Self-made banana peel graphene PE-RT super-thermal-conductive anti-scaling floor heating pipe and preparation method thereof
CN112876763A
Method for preparing isotropic high-thermal-conductivity composite material based on boron nitride
CN113912400A
High-thermal-conductivity PERT floor heating pipe and preparation method thereof
CN115139572A
Graphite powder casting coating and preparation method thereof
CN115156477A
Cited By
PERT floor heating pipe material and preparation method thereof
CN120209435A
Heat-conducting pert composite material suitable for floor heating pipes and preparation and application thereof
CN122772285A